(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2025)
Fires are one of the disasters that can threaten lives and property, especially in densely populated residential environments such as boarding houses. Kos Putri Kanaya Projo is one of the female boarding houses in East Ungaran, Semarang Regency, which is at high risk of fire due to residents’ negligence in using electrical equipment or gas stoves. This research aims to design and build an early fire detection system based on a microcontroller with the support of Internet of Things (IoT) technology. The system was developed using an ESP32 microcontroller connected to an MQ-2 sensor (smoke/gas), a PIR sensor (flame), and a DHT22 sensor (temperature/humidity). The system output consists of warning notifications on the Blynk application, a buzzer as an audio alarm, and information displayed on an LCD. The research method used is prototyping with the stages of design, implementation, testing, and system refinement. The test results show that the system is able to detect smoke, gas, high temperature, and flames with an accuracy of over 90% and provides warning notifications via the Blynk application with a response time of less than 10 seconds. Therefore, this system is effective as an early fire detection solution in boarding house environments, thereby enhancing safety and minimizing the risk of material loss and casualties.